2022
DOI: 10.1128/jvi.01630-21
|View full text |Cite
|
Sign up to set email alerts
|

SUMOylation of Matrix Protein M1 and Filamentous Morphology Collectively Contribute to the Replication and Virulence of Highly Pathogenic H5N1 Avian Influenza Viruses in Mammals

Abstract: The matrix protein (M1) of influenza A virus plays an important role in replication, assembly, and budding. A previous study found that aspartic acid (D) at position 30 and alanine (A) at position 215 of M1 contribute to the high pathogenicity of H5N1 viruses in mice, and double mutations of D to asparagine (N) at position 30 (D30N) and A to threonine (T) at position 215 (A215T) in M1 dramatically attenuate H5N1 viruses in mice. However, the underlying mechanisms by which these M1 mutations attenuate the virul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Amino acid sequences of SINER/GLF were observed at the cleavage site in HA, which is typical of viruses with low pathogenicity in poultry. Several amino acid substitutions that contribute to increased virulence or transmissibility of avian influenza viruses were detected in the H16N3 virus, including PB1 207K, PB1 436Y, PA 515T, M1 30D, and M1 215A ( 15 , 16 ). Subsequently, Bayesian time-resolved phylogenetic trees for the ORFs of the HA and NA genes of the H16N3 viruses (including the related sequences downloaded from GISAID and GenBank) were constructed to elucidate their genesis and evolutionary timeline.…”
Section: Observationmentioning
confidence: 99%
“…Amino acid sequences of SINER/GLF were observed at the cleavage site in HA, which is typical of viruses with low pathogenicity in poultry. Several amino acid substitutions that contribute to increased virulence or transmissibility of avian influenza viruses were detected in the H16N3 virus, including PB1 207K, PB1 436Y, PA 515T, M1 30D, and M1 215A ( 15 , 16 ). Subsequently, Bayesian time-resolved phylogenetic trees for the ORFs of the HA and NA genes of the H16N3 viruses (including the related sequences downloaded from GISAID and GenBank) were constructed to elucidate their genesis and evolutionary timeline.…”
Section: Observationmentioning
confidence: 99%
“…In addition, SUMO and target proteins can interact noncovalently through SIMs (51,52). Current studies have shown that multiple proteins of the IAV, including NS1, M1, NP, PB1, and PB2, can be modified by SU-MOylation (53)(54)(55)(56)(57). In this study, we found that NS2 contains a previously identified conserved SIM sequence in its C-terminal tail.…”
Section: Discussionmentioning
confidence: 59%
“…K356R and S409N mutations occurred in almost all human isolates in Anhui province 27 . Mutations associated with increased virulence and polymerase activity, such as M1‐30D, M1‐215A, M1‐41A, and NS1‐42S, were found in all human isolates in Anhui 28–30 . Mutations associated with mammalian adaptation, such as PB1‐368V, PB2‐535L, and PB2‐588V, occurred in most isolates, particularly in Wave 5 31,32 .…”
Section: Resultsmentioning
confidence: 98%